2012
DOI: 10.1111/j.1471-4159.2012.07666.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of neonatal ischemic brain damage using a 20‐HETE synthesis inhibitor

Abstract: 20-hydroxyeicosatetraenoic acid (20-HETE) is a cytochrome P450 (CYP) metabolite of arachidonic acid that that contributes to infarct size following focal cerebral ischemia. However, little is known about the role of 20-HETE in global cerebral ischemia or neonatal hypoxia-ischemia (H-I). The present study examined the effects of blockade of the synthesis of 20-HETE with HET0016 in neonatal piglets after H-I to determine if it protects highly vulnerable striatal neurons. Administration of HET0016 after H-I impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 52 publications
6
54
0
Order By: Relevance
“…ND, not detected. Recent studies reported that CYP4A immunoreactivity was detected in neurons in hippocampus and putamen (Renic et al, 2012;Yang et al, 2012). In this study, CYP4A immunoreactivity was also detected in neurons in contralateral cortex and striatum.…”
Section: Discussionsupporting
confidence: 67%
“…ND, not detected. Recent studies reported that CYP4A immunoreactivity was detected in neurons in hippocampus and putamen (Renic et al, 2012;Yang et al, 2012). In this study, CYP4A immunoreactivity was also detected in neurons in contralateral cortex and striatum.…”
Section: Discussionsupporting
confidence: 67%
“…26,31 In other studies, 20-HETE inhibition reduced lesion volume and neurodegeneration independent of CBF, suggesting a direct neuroprotective effect of 20-HETE inhibition. 17,18,32 In a global cerebral ischemia model in immature piglets similar in some ways to our model, Yang et al 17 showed direct neuroprotection after CA in piglets treated with HET0016. In that report, focal cortical CBF measured by laser Doppler was not affected by treatment with HET0016 at 5 minutes after resuscitation.…”
Section: Discussionsupporting
confidence: 65%
“…In our model, HET0016 was administered at resuscitation (versus 5 minutes after resuscitation in the other study), suggesting that inhibition of 20-HETE immediately on reperfusion might be necessary to inhibit the cascade of events that occurs at reperfusion. The dose of HET0016 was 10-fold lower in our study, 17 and it is possible that a higher dose of HET0016 may lose selectivity for inhibition of CYP4A/4 F enzymes and thus inhibit CYP2C/2 J enzymes responsible for synthesis of vasodilatory EETs. Nevertheless, these two studies in global ischemia suggest neuroprotective effects of HET0016 inhibition.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Such inhibitors have been shown to directly protect hippocampal slice cultures from oxygen-glucose deprivation [18]. CYP 4A is also expressed in striatal neurons of neonatal piglets, and early administration of the 20-HETE synthesis inhibitor N -hydroxy- N ′-(4-n-butyl-2-methylphenyl)formamidine (HET0016) [22] after reoxygenation in a piglet model of hypoxia followed by complete asphyxia partially protected striatal neurons without affecting the recovery of cerebral blood flow [23]. Direct effects of 20-HETE on neuronal signaling are supported by the observed increases in phosphorylation of N-methyl-D-aspartate receptors and Na,K-ATPase during infusion of 20-HETE into piglet putamen and by attenuation of phosphorylation at these same sites by HET0016 administration after HI [23].…”
Section: Introductionmentioning
confidence: 99%